Evaluation of the Potential of Lactobacillus paracasei Adjuncts for Flavor Compounds Development and Diversification in Short-Aged Cheddar Cheese - Stefanovic, Ewelina; Kilcawley, Kieran N.; Roces, Clara; Rea, Mary C.; O'Sullivan, Maurice; Sheehan, Jeremiah J.; McAuliffe, Olivia (Frontiers in Microbiology, 2018)
The non-starter microbiota of Cheddar cheese mostly comprises mesophilic lactobacilli, such as Lactobacillus casei, Lactobacillus paracasei, Lactobacillus rhamnosus and Lactobacillus plantarum. These bacteria are recognized for their potential to improve Cheddar cheese flavour when used as adjunct cultures. In this study, three strains of L. paracasei (DPC2071, DPC4206 and DPC4536) were evaluated for their contribution to the enhancement and diversification of flavour in short-aged Cheddar cheese. The strains were selected based on their previously determined genomic diversity, variability in proteolytic enzyme activities and metabolic capability in cheese model systems. The addition of adjunct cultures did not affect the gross composition or levels of lipolysis of the cheeses. The levels of free amino acids (FAA) in cheeses showed a significant increase after 28 days of ripening. However, the concentrations of individual amino acids in the cheeses did not significantly differ except for some amino acids (aspartic acid, threonine, serine, and tryptophan) at Day 14. Volatile profile analysis revealed that the main compounds that differentiated the cheeses were of lipid origin, such as long chain aldehydes, acids, ketones and lactones. This study demonstrated that the adjunct L. paracasei strains contributed to the development and diversification of compounds related to flavour in short-aged Cheddar cheeses.